2022
DOI: 10.3390/ani12212935
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Host Antiviral Innate Immunity by African Swine Fever Virus: A Review

Abstract: African swine fever (ASF), caused by African swine fever virus (ASFV), is a highly contagious and fatal disease found in swine. However, the viral proteins and mechanisms responsible for immune evasion are poorly understood, which has severely hindered the development of vaccines. This review mainly focuses on studies involving the innate antiviral immune response of the host and summarizes the latest studies on ASFV genes involved in interferon (IFN) signaling and inflammatory responses. We analyzed the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 87 publications
0
19
0
Order By: Relevance
“…Recent studies have demonstrated that several ASFV-encoded proteins targeting cGAS-STING pathway can inhibit IFN-I production in diverse manners ( Table 1 ) [ 25 ]. In this pathway, cyclic GMP-AMP synthase (cGAS), which was previously identified to be a cytosolic DNA sensor, can directly recognize and bind to the non-self ASFV DNA [ 37 ].…”
Section: Suppression Of Ifn-i Production and Ifn-induced Antiviral Re...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated that several ASFV-encoded proteins targeting cGAS-STING pathway can inhibit IFN-I production in diverse manners ( Table 1 ) [ 25 ]. In this pathway, cyclic GMP-AMP synthase (cGAS), which was previously identified to be a cytosolic DNA sensor, can directly recognize and bind to the non-self ASFV DNA [ 37 ].…”
Section: Suppression Of Ifn-i Production and Ifn-induced Antiviral Re...mentioning
confidence: 99%
“…To date, a few articles have already highlighted the negative impact of plentiful ASFV proteins on antiviral immune response [ 25 , 26 , 27 ]. However, several ASFV immunosuppressive proteins (e.g., pE184L, pD345L, pD117L) and novel immune evasion mechanisms have not been summarized.…”
Section: Introductionmentioning
confidence: 99%
“…As resistance to ASFV is known to correlate with a robust IFN response [ 5 ], the virus is predicted to have evolved a number of counter-strategies to inhibit the IFN response, a prediction that has been verified [ 6 ]. Therefore, deletion of virus genes inhibiting induction and/or impact of IFN is a logical choice for the construction of such an attenuated gene deletion virus vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…African swine fever (ASF) is an acute, febrile, and hemorrhagic disease in domestic and wild pigs that is caused by the African swine fever virus (ASFV). ASFV is a large-diameter icosahedral DNA virus, and the genome is a linear 170–190 kb double-stranded DNA [ 1 ]encoding 150–200 viral proteins, including 68 structural proteins and more than 100 non-structural proteins [ 2 ]; however, the functions of most proteins are still unknown [ 3 , 4 ]. ASF was first reported in Kenya in 1921 [ 5 ], and it subsequently became endemic in most of sub-Saharan Africa and Sardinia [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…ASFV spread outside Africa to the Iberian Peninsula, initially to Portugal in 1957 and 1960, and subsequently to Europe and Latin America, then it was eradicated from all Western Europe except Sardinia by 1995 [ 7 ]. In 2007, ASF caused a serious outbreaks in Georgia, subsequently spreading to other adjacent countries of Europe, including Ukraine and Russia [ 1 , 8 ]. In 2018, the first outbreak of ASF was reported in Liaoning, China [ 9 ].…”
Section: Introductionmentioning
confidence: 99%